Estimasi Dosis CT Scan Abdomen Nonkontras Dewasa Berdasarkan CTDIvol dan DLP RSUD NTB - Bayu Septiawan (Indonesian Journal of Applied Science and Technology, 2025)
Abdominal computed tomography (CT) is a widely used diagnostic imaging modality but may result in relatively high exposure to ionizing radiation. Therefore, radiation dose evaluation is necessary to ensure patient safety in accordance with optimization principles. This study aimed to analyze the distribution of radiation doses in non-contrast abdominal CT examinations for adult patients at RSUD Province of West Nusa Tenggara based on Computed Tomography Dose Index volume (CTDIvol) and Dose Length Product (DLP), and to compare the results with the Indonesian Diagnostic Reference Level (IDRL) established by BAPETEN. A descriptive quantitative method with an observational approach was applied to 60 adult patient data collected from July to August 2024. CTDIvol and DLP values were obtained from the CT scanner workstation and analyzed using descriptive statistics. The results showed an average CTDIvol of 14.86 mGy with a 75th percentile of 16 mGy, and an average DLP of 775.87 mGy·cm with a 75th percentile of 838 mGy·cm. Overall, the radiation dose values were below the IDRL limits set by BAPETEN in 2021, although several cases exceeded the reference. These findings indicate that the abdominal CT scanning protocol at RSUD Province of West Nusa Tenggara generally complies with radiation dose optimization standards.